PENGGUNAAN PENDEKATAN CAPITAL ASSET PRICING MODEL DAN METODE VARIANCE-COVARIANCE DALAM PROSES MANAJEMEN PORTOFOLIO SAHAM (Studi Kasus: Saham-Saham Kelompok Jakarta Islamic Index) - Ikhsan, Aulia; Ispriyanti, Dwi; Rahmawati, Rita (Jurnal Gaussian, 2014)
The great amount of risk arising from stock investment make investors create a portfolio in order to minimize it. To achieve this aim, a portfolio management in which consist of several processes is required. There are three important processes in portfolio management. First, the selection of stocks that will be selected into the portfolio by Capital Asset Pricing Model (CAPM). Second, portfolio optimization by defining the weight of fund allocation for every stock in portfolio by Mean Variance Efficient Portofolio (MVEP), and third, estimating the risk of the optimal portfolio by Variance-Covariance. There are seven stocks picked into portfolio through the research done by Jakarta Islamic Index (JII) group, where the biggest fund allocation given to stock of EXCL (PT XL Axiata, Tbk) and the smallest fund allocation given to stock of ITMG (PT Indo Tambangraya Megah, Tbk). The amount of loss that estimated on 95% confidence level is 2,65% from initial capital invested on stock portfolio during one day holding period after portfolio were created.